Long-term Imaging of the Lungs After Sealant Bronchoscopic Lung Volume Reduction. Issue 6 (November 2016) - Lieberman, Sivan; Shulimzon, Tiberiu R.; Davidson, Tima; Marom, Edith M.
Abstract : Purpose: The aim of the study was to assess the pulmonary temporal changes after bronchoscopic lung volume reduction (BLVR) using sealants for treatment of emphysema. Materials and Methods: We retrospectively assessed all chest computerized tomography (CT) and F-18 fluorodeoxyglucose (FDG) positron emission tomography CT scans of patients treated at our institution with BLVR. Results: Eleven patients were treated with sealants: 4 with biological sealants and 7 with synthetic sealants. The first CT scan after biological sealant treatment showed no abnormalities in 8 lobes and 5 nodules, and 3 consolidations in 7 lobes. All findings resolved within 3 months, except for a nodule that decreased after 2 months and remained stable for 9 years. The first CT scan after utilizing the synthetic sealant showed abnormalities in each treated lobe: 19 nodules/masses (16 cavitary, 3 solid) and 3 consolidations. Follow-up CT scans were available for 16 nodules/masses: 1 resolved, 12 slowly decreased in size, 1 remained unchanged, and 2 grew. Of 3 consolidations 1 resolved and 2 decreased in size. FDG positron emission tomography CT scans performed in 2 patients showed FDG uptake higher than mediastinal background activity in 2 nodules in the same patient. Conclusions: Pulmonary changes after BLVR are variable. After treatment with biological sealants, most findings resolve within 3 months. In contrast, after synthetic sealants, although the majority regress over time, some show waxing and waning in growth that can mimic malignancy. FDG uptake in some of these lesions is suggestive of chronic inflammation. Radiologists should be aware of the spectrum of these pulmonary changes to avoid misdiagnosis of lung cancer.